The Clinical and Radiological Outcome of Bovine Hydroxyapatite (Bio Hydrox) as Bone Graft - Arifin; Ferdiansyah Mahyudin; Mouli Edward (Journal Orthopaedi and Traumatology Surabaya)
Background: Bone grafting is a surgical procedure that involves transplanting material to enhance bone healing through osteogenesis, osteoconduction, and osteoinduction. While autografting has long been considered the gold standard, it has limitations, including a restricted supply and donor site morbidity. These limitations, along with those associated with allografts, have led to the development of bovine hydroxyapatite (BHA) as a bone graft substitute. This study aimed to evaluate the clinical and radiological outcomes of BHA. Methods: This descriptive study used a consecutive sampling design, including all trauma patients who received BHA at our hospital between 2016 and 2018. The BHA was obtained from the tissue bank at our institution. The clinical and radiological outcomes were evaluated, and the data was tabulated and analyzed descriptively. Results: Of the 56 patients who underwent surgery with BHA, most (80.36%) had excellent outcomes, 12.5% had good outcomes, 3.57% had fair outcomes, and 3.57% had poor outcomes. Conclusion: Bovine hydroxyapatite can be considered an alternative bone graft to support the bone healing process.